Akibat Hukum dan Upaya Penanggulangan Terlambat Mendaftarkan Akta Kelahiran Anak Ditinjau dari Undang-Undang Nomor 23 Tahun 2006 Tentang Administrasi Kependudukan - Akris Siluwanus Sanu; Agustinus Hedewata; Helsina F.Pello (LPPM Universitas Sains dan Teknologi Komputer, 2023)
The purpose of this research is to analyse the legal consequences and countermeasures for late registration of a child's birth certificate in terms of Law No. 23/2006 on population administration. This research was conducted at the Civil Registration Office, Rote Ndao Regency. This research is an empirical legal research, which is conducted by looking at the reality that exists in field practice. This approach is also known as a sociological approach which is carried out directly to the field. Based on the results of the research conducted, it is found that: (1) The legal consequences of the delay in registering a Child Birth Certificate in terms of Law Number 23 of 2006 concerning Population Administration (Case Study of the Civil Registration Office of Rote Ndao Regency) are that the child does not get legal certainty about himself, does not have legal status as a child and the parents will have difficulties in fulfilling the child's needs in terms of public services. (2) Efforts to overcome the delay in registering a child's birth certificate at the Civil Registration Office of Rote Ndao Regency, namely providing oral policy in the form of convenience in the requirements for making birth certificates, as an effort to overcome obstacles related to the absence of legislation governing child birth certificates.